2022
DOI: 10.3390/md20010064
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Composition, Antioxidant and Antimicrobial Activities of Cystoseira compressa during Seasonal Growth

Abstract: The underexplored biodiversity of seaweeds has recently drawn great attention from researchers to find the bioactive compounds that might contribute to the growth of the blue economy. In this study, we aimed to explore the effect of seasonal growth (from May to September) on the in vitro antioxidant (FRAP, DPPH, and ORAC) and antimicrobial effects (MIC and MBC) of Cystoseira compressa collected in the Central Adriatic Sea. Algal compounds were analyzed by UPLC-PDA-ESI-QTOF, and TPC and TTC were determined. Fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 52 publications
4
41
1
Order By: Relevance
“…In agreement, Čagalj et al registered an ORAC value of 72.1 μmol TE g −1 extract in an ethanolic extract of Cystoseira compressa. 45 Ferreres et al also reported a high antioxidant activity, including lipid peroxidation inhibition ability for E. selaginoides (EC 50 of 7.55 mg mL −1 of dry weight), which was positively correlated with their phlorotannins content. 40 However, Pinteus et al evaluated the ORAC of E. selaginoides (methanolic extract), collected in the same coast line (Peniche coast), and registered 3396.73 μmol TE g −1 extract.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In agreement, Čagalj et al registered an ORAC value of 72.1 μmol TE g −1 extract in an ethanolic extract of Cystoseira compressa. 45 Ferreres et al also reported a high antioxidant activity, including lipid peroxidation inhibition ability for E. selaginoides (EC 50 of 7.55 mg mL −1 of dry weight), which was positively correlated with their phlorotannins content. 40 However, Pinteus et al evaluated the ORAC of E. selaginoides (methanolic extract), collected in the same coast line (Peniche coast), and registered 3396.73 μmol TE g −1 extract.…”
Section: Discussionmentioning
confidence: 90%
“…In agreement, Čagalj et al . registered an ORAC value of 72.1 μmol TE g −1 extract in an ethanolic extract of Cystoseira compressa 45 . Ferreres et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymer has shown significant antibacterial activity against a wide range of human pathogens, including Bacillus subtilis , Staphylococcus aureus , Lactobacillus acidophilus , Escherichia coli , Pseudomonas aeruginosa , Proteus mirabilis , and Vibrio cholerae ( Pushparaj et al, 2014 ). According to a study, gram-positive bacteria are more vulnerable to seaweed extracts than gram-negative bacteria, and this vulnerability to algal extracts is attributable to the differences in the structure and content of their cell walls ( Čagalj et al, 2022 ). Additionally, K. alvarezii carrageenan has shown excellent suppression of Mycobacterium tuberculosis ( Mayakrishnan et al, 2015 ).…”
Section: Carrageenan In Food and Medical Applicationsmentioning
confidence: 99%
“…Seaweeds can be produced without arable land, freshwater, or fertilizers [ 4 ]. Seaweed biodiversity has recently attracted a lot of attention from researchers to find bioactive compounds that could contribute to the growth of the blue economy [ 5 ]. Marine organisms are considered as a potential source of biologically active compounds, but at the same time their chemical composition can provide biologically active compounds for drug development [ 6 ].…”
Section: Introductionmentioning
confidence: 99%